Desarrollo e implementación de la gestión por competencias como una herramienta de manejo del talento humano, a través de técnicas que se ajusten a la estructura de la Fundación Maquita Cushunchic - Leonor Jácome, Shajaira Lubuguin (2006)
The purpose of this paper is to present the Method Competency Management as a methodology for Human Resource Management in Maquita Cushunchic Foundation, the same that has been developed considering the practical and technical needs of the institution as well as the to provide innovative and creative ideas for human Development professionals optimize human, material and time spent in each process.